Profil Keterampilan Berpikir Kritis Mahasiswa Calon Guru pada Materi IPA - M. Misbachul Huda (STKIP AL HIKMAH SURABAYA, 2025)
Critical thinking skills play a fundamental role for pre-service teacher students in addressing the complexities of 21st-century education. These skills equip future teachers with the ability to filter credible information, identify biases, and construct logical arguments, enabling them to guide students to become independent and reflective thinkers. Therefore, it is essential to map the critical thinking skills of pre-service teacher students. This research is a quantitative descriptive study using an ex-post facto approach. Critical thinking skills were measured using a test instrument based on five indicators: basic clarification, interpretation, explanation, analysis, and inference. The results show that the critical thinking skills of pre-service teacher students fall into three categories: very good, good, and fair. The most dominant category is good, which implies the importance of developing critical thinking skills among pre-service teachers in the learning process.